**Answer:**

x + 3

**Step-by-step explanation:**

Step 1 :

2

Simplify —

1

Equation at the end of step 1 :

x

(((5•—)-2)-x)+(2•x)

x

Step 2 :

x

Simplify —

x

Equation at the end of step 2 :

(((5 • 1) - 2) - x) + 2x

Step 3 :

Final result :

x + 3

Processing ends successfully

**plz mark me as brainliest :)**

(0,-7)

-7=11(0)+4

-7=0+4

-7 is not 4 -----not a solution

(-1,-7)

-7=11(-1)+4

-7=-11+4

-7=-7 ----solution

(1,-7)

-7=11(1)+4

-7=11+4

-7=15

-7 is not 15 ----not a solution

(2,26)

26=11(2)+4

26=22+4

26=26 ----soltion

(-1, -7) & (2, 26) are solutions to the equation

Answer:

Option 1

Step-by-step explanation:

(3m/n)⁴ = (3⁴×m⁴)/n⁴

= 81m⁴/n⁴

**Answer:**

x =20

**Step-by-step explanation:**

**Answer:**

A) -2 + x = -3 is equal to x = -1 is True!

**Step-by-step explanation:**

-2 + x = -3

+2 +2

x = -1

x = -1

Correct

x -2 = -3

+2 +2

x = -1

x = 1.5 is False

-2 - x = -3

+2 +2

-x = -1 or x = 1

x = -5 is False

-2 + x = -3

+2 +2

x = -1

x = -5 is False